Penanaman nilai toleransi, pluralisme, multikulturalisme pada generasi muda di tengah polarisasi digital - al-irsyady, suci oktavia (Maliki Interdisciplinary Journal, 2026)
Instilling the values ​​of tolerance, pluralism, and multiculturalism in the younger generation is crucial amidst technological developments and the rise of digital polarization. Social media, as the primary platform for interaction for the younger generation, has not only positive but also negative impacts. These impacts can trigger conflict through the spread of misinformation and hate speech. This situation demands the strengthening of values ​​that maintain social harmony. Tolerance plays a role in fostering mutual respect. Pluralism encourages active community involvement in diversity, while multiculturalism emphasizes acceptance of existing differences. These values ​​can be instilled through education and increased digital literacy. The roles of families, schools, and communities are also crucial in instilling these values. Wise use of social media is also a strategy for spreading positive values. Thus, the younger generation is expected to be able to face the challenges of digital polarization and contribute to creating a peaceful, harmonious, and just social life.